Characterization of herpes simplex virus type 2 transcription during latent infection of mouse trigeminal ganglia. - Mitchell, W J (1990)
Using a cornea trigeminal ganglion model, we have investigated transcription by herpes simplex virus type 2 (HSV-2) during latency in mice. Latency was verified 2 months postinoculation by reactivation of HSV-2 after explant cocultivation of trigeminal ganglia from the majority of mice (83%). Transcription during latent HSV-2 infection was limited to the repeat regions of the viral genome as determined by in situ hybridization using restriction fragment probes representing 100% of the HSV-2 genome. Further mapping of the positively hybridizing region by using subfragments showed that transcription occurred from approximately 11.5 kb of contiguous DNA fragments. A 1.0-kb PvuI-BamHI fragment within the BamHI F fragment and a 0.3-kb BamHI-SalI fragment and a 3.4-kb SalI-BamHI fragment within the BamHI P fragment hybridized more strongly than other subfragments in in situ hybridization experiments. All positive signals were confined to the nucleus. The RNA that hybridized to the 3.4-kb SalI-BamHI DNA fragment probe by in situ hybridization corresponded to a 2.3-kb transcript on Northern (RNA) blots. Under our conditions for Northern blot hybridization, the 3.4-kb SalI-BamHI probe of HSV-2 hybridized to a limited degree with the latency-associated transcripts of HSV-1. Shorter spliced species of latency-associated transcript RNA, which are seen during HSV-1 latency, have not been detected in latent HSV-2 RNA. However, viral gene expression during HSV-2 latency appears to be very similar to that during HSV-1 latency.